Quality Of Duck Eggs with A Storage Time of 21 Days In The Low Lands In The Jimbaran Area - I. B. A., Indrayoga; Wijana, I W.; Wirapartha, M. (Jurnal Peternakan Tropika, 2019)
This study aims to determine the quality of duck eggs stored in the lowlands of Bukit Jimbaran for 21 days. The study was carried out in the Jimbaran hill area, while in the Poultry Laboratory in Denpasar from preparation for egg laying to data processing for 4 weeks. The design of the study used Completely Randomized Design (CRD), consisting of 4 treatments namely eggs without storage (0 days / control), 7 days egg storage, 14 days egg storage, 21 days egg storage, each treatment using 4 replications each replication using 4 eggs Variables observed were egg weight, egg shape index, eggshell thickness, egg pH, egg yolk, high egg white, haugh unit (HU). The results showed the effect of storage on increasing egg pH, decreased egg white height and haught units (HU) without storage (0 days / control), storage 7 days, 14 days and 21 days had significantly different results (P <0.05). Regarding egg weight, egg shape index, eggshell thickness and egg yolk without storage (0 days / control), storage for 7 days, 14 days and 21 days gave no significant difference (P> 0.05). Based on the results of the study concluded that duck eggs without storage (0 days / control), storage for 7, 14 and 21 days at room temperature in the Jimbaran area did not affect egg weight, egg shape index, shell thickness and egg yolk color, but storage duck eggs for 21 days have an effect on increasing egg pH, decreasing egg white and haugh unit (HU). However, the quality of duck eggs during storage for 21 days still has grade A and duck eggs are still suitable for consumption at 21 days of storage. Keywords : duck eggs, storage time, low land, Jimbaran, egg quality.